2013
DOI: 10.1002/ejoc.201300439
|View full text |Cite
|
Sign up to set email alerts
|

On the Configurational Stability of Chiral Heteroatom‐Substituted [D1]Methylpalladium Complexes as Intermediates of Stille and Suzuki–Miyaura Cross‐Coupling Reactions

Abstract: Enantiomerically pure (S)-tributylstannyl[D1]methanol and (R)- and (S)-tributylstannyl[D1]methyl benzoates were Stille-coupled with bromobenzene and benzoyl chloride in 1,4-dioxane and toluene using [(Ph3P)4Pd] or [(Ph3P)2PdCl2] either alone or in combination with CuCN as cocatalyst at temperatures up to 80 °C. The products were found to be enantiomerically pure. (R)- and (S)-N-(tributylstannyl[D1]methyl)phthalimides gave enantiomerically pure products with benzoyl chloride, but with bromobenzene protected phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 38 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…In addition, Hammerschmidt and Krizkova reported a Pd-catalyzed cross-coupling of deuterium-incorporated 1,1-borylsilyl reagents with bromobenzene (Scheme 3 B). 19 After sequential oxidation and derivatization to the corresponding Mosher ester, the product was subjected to 1 H NMR analysis to demonstrate that a net retention of configuration had occurred. The stereochemical outcome is consistent with the results obtained by Woerpel and Soderquist.…”
Section: Cross-coupling Of 1° Alkylboron Compoundsmentioning
confidence: 99%
“…In addition, Hammerschmidt and Krizkova reported a Pd-catalyzed cross-coupling of deuterium-incorporated 1,1-borylsilyl reagents with bromobenzene (Scheme 3 B). 19 After sequential oxidation and derivatization to the corresponding Mosher ester, the product was subjected to 1 H NMR analysis to demonstrate that a net retention of configuration had occurred. The stereochemical outcome is consistent with the results obtained by Woerpel and Soderquist.…”
Section: Cross-coupling Of 1° Alkylboron Compoundsmentioning
confidence: 99%
“…Traditional methods for the preparation of α-acyloxy ketones focus on the substitution reactions of α-halo carbonyl compounds with alkaline carboxylates or carboxylic acids [6–7], and transition-metal-catalyzed direct oxidative coupling reactions of carbonyl compounds with carboxylic acids (or their surrogates) [89]. Recently, robust approaches using organohypervalent iodine reagents and peroxide-mediated oxidative coupling have been developed [1011].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, α-acetoxyaryl ketones have attracted considerable interest because this structural motif is found in a variety of biologically active natural products and pharmaceuticals, and α-acetoxyaryl ketones are widely used as synthetic intermediates [ 1 5 ]. Traditional methods for the preparation of α-acyloxy ketones focus on the substitution reactions of α-halo carbonyl compounds with alkaline carboxylates or carboxylic acids [ 6 – 7 ], and transition-metal-catalyzed direct oxidative coupling reactions of carbonyl compounds with carboxylic acids (or their surrogates) [ 8 9 ]. Recently, robust approaches using organohypervalent iodine reagents and peroxide-mediated oxidative coupling have been developed [ 10 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Next, the reaction of a stoichiometric amount of a chiral silylcopper­(I) complex, which was prepared in situ from CuCl, L4 ·HBF 4 , PhMe 2 SiB­(pin), and NaO t Bu (1:1:1:2), with deuterated benzaldehyde-α- d 1 ( 1b - d ) was also performed without any proton sources (Figure c). The reaction gave, after addition of acetic acid, chiral deuterated benzyl silyl ether 5b - d with the S configuration. , The stereochemical outcomes observed in the three-component reactions indicated that the copper-mediated [1,2]-Brook rearrangement proceeded with inversion of configuration ( C → D ; Figure a). , Additionally, comparison of the absolute configuration of 5b - d with that of benzhydryl silyl ether 3ba obtained by the coupling reaction with aryl bromide (Figure d) indicated that the Cu/Pd transmetalation between stereodefined α-silyloxybenzylcopper­(I) species D and arylpalladium­(II) intermediate F could occur with retention of configuration ( D → G ; Figure a) …”
mentioning
confidence: 99%